If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+4/2=x-6/5
We simplify the equation to the form, which is simple to understand
3x+4/2=x-6/5
Simplifying:
3x+2=x-6/5
Simplifying:
3x+2=x-1.2
We move all terms containing x to the left and all other terms to the right.
+3x-1x=-1.2-2
We simplify left and right side of the equation.
+2x=-3.2
We divide both sides of the equation by 2 to get x.
x=-1.6
| 8x(n)=20 | | -4t-2=-3t+5 | | 2.9(1.1x-6.3)-8x= | | 5.5q-1.3-5.4q=0.9q-2.6 | | 2n-5(2n+4)=12 | | 4x(n)=1 | | 10(20+C)=900 | | 24c=96 | | x+54=90 | | 9(x^2+1)=x+8 | | (6x-1)(x+5)=7 | | x+56=458 | | 5x=-13 | | 15x^2-14x=-3 | | x=4(3-2)+6/8 | | 3m-2(m-1)+11=16 | | 15p^4+61p^3q+4p^2q^2= | | 4c+8=-55+3c | | -3(m-3)= | | P+7p-5p= | | 8(3m+7)= | | p-24=13 | | 12x-32=8x | | 7(2m-3)= | | 12x+(-352/7)=20 | | 1/4(4m-8)= | | 3=(4x+1)(x-7) | | r^2-12r=-35 | | 1/2(m-2)= | | 14+2x=1.50+20x | | 6(m-5)= | | 3(x+1)=-3(2x-4)+9 |